Association of IL4R-rs1805016 and IL6R-rs8192284 polymorphisms with clinical dengue in children from Colombian populations. Issue 1 (January 2019) - Useche, Yerly M.; Restrepo, Berta N.; Salgado, Doris M.; Narváez, Carlos F.; Campo, Omer; Bedoya, Gabriel
Abstract: Background: Etiologic studies provide evidence that IL-4R and IL-6R receptors may play important roles in the regulatory mechanisms of the development of clinical dengue, especially in children which is a segment of the population with high severe dengue risk. Moreover, the allele frequencies and genetic associations may be influenced by the populational genetic background. Therefore, we performed a case-control study to evaluate possible associations between SNPs in IL4R and IL6R genes and clinical dengue in children from two Colombian populations. Methods: We genotyped the rs1805016 ( IL4R ) and rs8192284 ( IL6R ) by PCR-RFLP method, in 298 symptomatic children and 648 asymptomatic controls. Three individual genetic ancestral proportions (APs) (European, Amerindian, African) were inferred by genotyping 29 AIMs (Ancestry informative markers). The variables gender, APs, and the population of origin were used like confusion variables. Results: We found IL4R -rs1805016 GG genotype and G-allele carriers and IL6R- rs8192284 AA genotype associated with clinical dengue in the pooled and Huila samples. Nevertheless, we found no association of these polymorphisms in the sample of Antioquia. Conclusions: For the first time, we report SNPs in IL4R and IL6R genes associated with clinical dengue, which contributes to understanding the genetic susceptibility to dengue disease. Moreover, these results may be influenced by genetic background and must be evaluated through functional analysis.